MSMEs Awareness in Halal Certification from an Operations Management Perspective - Abi Anwar, Umari Abdrurrahim; Nurhakim, Haditsa Qur'aini; Hamidah, Karina; Azzahra, Shinta Fauziah; Arkani, Zalva Hijatul (UPT Publikasi Ilmiah UNISBA, 2024)
Providing halal certification is considered as one of the tools that can strengthen the position of Indonesian MSMEs. This is due to the ability of MSME products that have halal status to become a competitive advantage for Indonesia on the international stage. This study will analyze the factors that can increase the awareness of MSMEs in Indonesia regarding the importance of obtaining halal certification. This research uses descriptive methods through survey techniques. The survey technique used is a questionnaire technique that must be filled in by the subject and also conducts opinion polls, as well as in-depth interviews with a sample of respondents selected based on the requirements for the length of time MSMEs have been established, the type of MSME business, and ownership of current halal certification. MSMEs have realized the importance of halal certification even though many of them have not processed it due to a lack of education. However, even though they are not yet halal certified, from an operations management perspective, the production process that is carried out is halal by ensuring that both the materials used and the processes carried out are in accordance with Islamic law.